THE EFFECT OF AGE OF LEARNING (AOL) AND INTERLANGUAGE ON ENGLISH ORAL UTTERANCE ACCURACY AND COMPLEXITY OF ASIAN EFL LEARNERS WITH ‘TENSES-LESS’ L1 BACKGROUND - Yunita Rahmasari; Horace Chen; Ting Zhang (JOEL: Journal of Educational and Language Research, 2023)
The younger age of English-language learning has often been associated with the success of English as a second or a foreign language learning. Hence, this study aims at investigating whether language learners with younger ‘Age of Learning’ (AoL) perform better accuracy and produce more complex English oral utterances than those of older-AoL. The study participants were six international graduate students at an Australian university. They are from China, Indonesia, and Vietnam and share similar “tenses-less” L1 background. The study participants were grouped into two cohorts (younger-AoL and older-Aol). The results showed that younger-AoL participants generally have higher syntactic complexity, lexical complexity, and accuracies than the older group in their English oral utterances. However, the older-AoL group outperformed participants with younger-AoL in the past-tenses accuracy. In addition, despite having younger AoLs, none of the participants in the younger-AoL group achieves nativelike accuracy.